C-type lectin domain family 3 member B (CLEC3B) inhibits triple-negative breast cancer chemoresistance via inducing ferroptosis - Lina Peng; Wenhui Yan; Juanjuan Mei; Hongbo Lan; Fei Chen; Kun Xie; Jingshuang Wang; Futing Mu; Xunpeng Luo; Yanan Liu (European Journal of Medical Research)
Abstract Background and aims Cisplatin is one of effect chemotherapeutic drugs for triple-negative breast cancer (TNBC). However, cisplatin chemoresistance often generate in a notable proportion of TNBC patients, leading therapeutic failure. Thus, identification of key regulatory mechanisms for chemoresistance is important. Here, we aimed to study the functions and regulatory mechanisms of CLEC3B in cisplatin chemoresistance in TNBC. Methods MTT assay, colony formation assay and Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay were employed to investigate the role of CLEC3B in cisplatin (CDDP) resistance in TNBC. Fe2+ Current assay and MDA level assay were used to determine CLEC3B’s role in ferroptosis. Co-Immunoprecipitation was used to determine the interaction proteins of CLEC3B. Western blotting assay were performed to determine CLEC3B’s role in solute carrier family 39 member 8 (SLC39A8) and solute carrier family 39 member 14 (SLC39A14) levels. Results Here, we find that CLEC3B was downregulated in TNBC tissues, especially in relapsed TNBC tissues. TNBC patients with high CLEC3B levels had better prognosis than those with low CLEC3B levels after chemotherapy. Functional assays showed that CLEC3B promoted CDDP chemosensitivity. Mechanistic assays found that CLEC3B promoted CDDP chemosensitivity via inducing ferroptosis. Moreover, CLEC3B interacted with SLC39A8 and SLC39A14 and knockdown of them reversed the effect of CLEC3B overexpression on chemosensitivity. Conclusions In summary, CLEC3B promotes chemosensitivity via interacting with SLC39A8 and SLC39A14 to induce ferroptosis.